On-demand ultrasonography assessment in the most symptomatic joint supports the 8-joint score system for management of rheumatoid arthritis patients. Issue 2 (4th March 2017) - Yoshimi, Ryusuke; Takeno, Mitsuhiro; Toyota, Yukihiro; Tsuchida, Naomi; Sugiyama, Yumiko; Kunishita, Yosuke; Kishimoto, Daiga; Kamiyama, Reikou; Minegishi, Kaoru; Hama, Maasa; Kirino, Yohei; Ishigatsubo, Yoshiaki; et al.
Abstract: Objectives : To investigate whether on-demand ultrasonography (US) assessment alongside a routine examination is useful in the management of rheumatoid arthritis (RA). Methods : US was performed in eight (bilateral MCP 2, 3, wrist and knee) joints as the routine in a cumulative total of 406 RA patients. The most symptomatic joint other than the routine joints was additionally scanned. Power Doppler (PD) and gray-scale images were scored semiquantitatively. Eight-joint scores were calculated as the sum of individual scores for the routine joints. Results : The most symptomatic joint was found among the routine joints in 209 patients (Group A) and in other joints in 148 (Group B). The PD scores of the most symptomatic joint correlated well with the 8-joint scores in Group A (rs  = 0.66), but not in Group B (rs  = 0.33). The sensitivity and specificity of assessment of the most symptomatic joint for routine assessment positivity were high (84.0% and 100%, respectively) in Group A, but low (50.0% and 61.8%, respectively) in Group B. Additional examination detected synovitis in 38% of Group B with negative results in the routine. Conclusions : On-demand US assessment in the most symptomatic joint, combined with the routine assessment, is useful for detecting RA synovitis.